2011
DOI: 10.1080/15567265.2011.597492
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nanostructured Capillary Wicks for Passive Two-Phase Heat Transport

Abstract: The major factors limiting the thermal performance of passive two-phase heat-spreading devices are the ability of the wick structures to transport liquid by means of capillary forces and the thermal resistance posed by the wicks. Nano-scale geometric enhancements to the wick structure, through the use of carbon nanotubes and metallic nanowires, promise to enhance the capillary transport while at the same time decreasing the thermal resistance due to their high intrinsic thermal conductivity. We analyze the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 42 publications
(59 reference statements)
0
23
1
Order By: Relevance
“…Analysis as a function of nanowire density found that the maximum wicking length occurred at a non-dimensional pitch of 5 due to the tradeoff between capillary pressure and permeability; however, the maximum wicking lengths were only on the order of 1 cm even for modest heat loads due to the low permeability of the structure. This suggested that use of nanowick arrays over a large area on a heated smooth substrate would perform poorly [218].…”
Section: Nanowire Array Wicksmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis as a function of nanowire density found that the maximum wicking length occurred at a non-dimensional pitch of 5 due to the tradeoff between capillary pressure and permeability; however, the maximum wicking lengths were only on the order of 1 cm even for modest heat loads due to the low permeability of the structure. This suggested that use of nanowick arrays over a large area on a heated smooth substrate would perform poorly [218].…”
Section: Nanowire Array Wicksmentioning
confidence: 99%
“…Ranjan et al [218] considered evaporation from a uniform nanowire array fed by capillary action. The evaporative resistance of the liquid meniscus formed in the array was computed numerically using the previously developed model discussed in Section 3.2.3 [155].…”
Section: Nanowire Array Wicksmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been achieved through patterning the wick structure [3] or using biporous wicks [4] to enable continuous feeding of liquid to the evaporator under boiling conditions. Alternate strategies aim to reduce the evaporator wick thermal resistance and preserve operation in the evaporative regime (avoiding boiling) using thin nanostructure arrays [5,6] or thin monoporous copper particles with arterial liquid return paths [7,8].…”
Section: Introductionmentioning
confidence: 99%